Bilateral Avascular Necrosis and Pelvic Insufficiency Fractures Developing after Pelvic Radiotherapy in a Patient with Prostate Cancer: A Case Report - Hidayet Sarı; Nurettin İrem Örnek; Hamza Sucuoğlu; Rana Kaynar; Murat Uludağ (Galenos Yayinevi, 2016)
Prostate cancer is one of the most common malignancies in men. Pelvic radiotherapy is commonly used in both radical and palliative treatment for prostate cancer. Radiation-induced adverse effects might be seen on adjacent healthy tissues (such as vessels, bones and soft tissues) with the exception of targeted area. Particularly several years after radiotherapy, low back and hip pain may occur due to bone edema, necrosis or fractures. In these cases, whether complaints due to the degenerative, metastatic or radiotherapy complications must be examined and appropriate treatment should be arranged. For this purpose, we present our elderly patient who received radiotherapy for prostate cancer, and thereafter, developed bilateral avascular hip necrosis and pelvic insufficiency fractures.